Testing the Weak Form of Efficiency of the Indian Stock Market : A Study of Selected Stocks Listed on the NSE - Nalini, R. (Indian Journal of Research in Capital Markets, 2015)
The efficient market hypothesis (EMH) is playing a crucial role in pricing and allocation of capital. In efficient capital markets, the security prices are assumed to quickly absorb all relevant information and reflect the same in their security prices. So, no investor in an efficient market will be able to earn abnormal profits. Fama (1970) categorized the EMH into three levels namely, weak form, semi strong form, and strong form. The purpose of this study was to test whether the weak form of efficient market hypothesis holds true for the Indian stock market. The study is empirical in nature and is based upon secondary data. The data used in the study consisted of monthly adjusted closing prices of 36 stocks of companies traded on the NSE. The stocks considered belong to different sectors such as automobile, banking, cement, FMCG, pharmaceutical, and textile sectors. The data for a 10-year period - from January 1, 2003 to December 31, 2013 were collected and runs test was applied to test the weak form of efficiency. The results showed that the price movements in share prices of National Stock Exchange of the Indian stock market are random in behavior, implying that one cannot use the historical prices for predicting the future prices. That is, all the information contained in historical prices is not revealed by the current prices. This proved that the weak form of the market efficiency hypothesis is applicable in the National Stock Exchange (based upon the share price movement of 36 sample companies chosen for the study).